Uma avaliação da liderança do diretor de escola a partir de microdados da Prova Brasil - Pinto, Vera Regina Ramos (2016)
Principals have been increasingly blamed and charged for the proper functioning of their school, the way teachers teach and how much students learn. In addition, the majority of school principals have graduation in pedagogy, but their assignments encompass more knowledge than that, requiring them several activities in management, being demanded to have leadership qualifications. Leadership is now seen as a guarantee of quality and educational reforms; it is a fundamental component for the training of school staff and also considered one of the main influences in transforming educational practices. Successful leadership plays an important role in student learning, being the second factor, among all school-related, that most contributes to students learning, losing only to the classes themselves. This thesis aimed to verify the extent to which the leadership of Brazilian principals has contributed to the improvement of students performance, reflected in the results of external evaluations, in this case the school’s IDEB. Based on the use of microdata from the contextual questionnaires answered by principals and teachers on the occasion of Prova Brasil 2013, it was possible to measure dimensions of successful leadership, to propose a model that relates these dimensions to student performance, reflected in the results of IDEB, as well as analyzing these relationships.